PENGARUH BIG BOOK KONSEP PENGUKURAN PADA KEMAMPUAN BERPIKIR LOGIS ANAK 4-5 TAHUN - Abelia, Citra Tasya; Ilhami, Akmillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to determine the effect of using a “Big Book” based on measurement concepts on the logical thinking ability of children aged 4–5 years. This research was conducted in a kindergarten (TK Al-Kautsar Indralaya) using a one-group pretest-posttest design. Sixteen children were given a pretest to assess baseline logical thinking skills, then participated in learning activities using the Big Book media over a two-week period, followed by a posttest. Data were collected through structured observation with an instrument covering four indicators of logical thinking (understanding cause-effect, classifying, drawing conclusions, and problem-solving). The data were analyzed with descriptive statistics and a paired t-test. The results showed a significant improvement in children’s logical thinking after using the Big Book. The average posttest score was higher than the pretest score, and 100% of children reached at least the expected development category. Statistical analysis confirmed a significant difference between pretest and posttest scores (p < 0.001). These findings indicate that the Big Book with measurement concepts is effective in enhancing logical thinking abilities in early childhood. The Big Book’s interactive and concrete learning experience helped children grasp measurement concepts (such as size, length, weight) in a fun way, which in turn improved their reasoning skills.